2020
DOI: 10.1177/0047287520919522
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Demand Forecasting: A Decomposed Deep Learning Approach

Abstract: Tourism planners rely on accurate demand forecasting. However, despite numerous advancements, crucial methodological issues remain unaddressed. This study aims to further improve the modeling accuracy and advance the artificial intelligence (AI)-based tourism demand forecasting methods. Deep learning models that predict tourism demand are often highly complex and encounter overfitting, which is mainly caused by two underlying problems: (1) access to limited data volumes and (2) additional explanatory variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 58 publications
0
59
0
3
Order By: Relevance
“…Social media data is an extensive source of information that can be quantified. For example, big data is currently being used to forecast both hospitality (Antonio et al, 2019) and tourism demand (Zhang et al, 2020). This appears to be another fertile ground for hospitality and tourism research.…”
Section: The Future Of Tourism Economics Researchmentioning
confidence: 99%
“…Social media data is an extensive source of information that can be quantified. For example, big data is currently being used to forecast both hospitality (Antonio et al, 2019) and tourism demand (Zhang et al, 2020). This appears to be another fertile ground for hospitality and tourism research.…”
Section: The Future Of Tourism Economics Researchmentioning
confidence: 99%
“…Several prediction models are available in the field of TD prediction. In [8], the authors suggested that these methods are classified into time-series, AI, and econometric models, but TD prediction is usually done using time-series and econometric models [33].…”
Section: Tourism Demand Predictionmentioning
confidence: 99%
“…Most of the existing studies in TD prediction are based on the quantitative approach; they normally present a model using training data from historical tourist arrival volumes (TAVs) and other TD predictors [7,8]. Web technology advancements have made search engines an essential tool for tourists when planning their trips, especially in getting relevant information on their areas of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Uma boa previsão da demanda proporcionará menor estoque, custo financeiro e tempo de entrega, maior previsibilidade e satisfação do cliente (ZHANG et al, 2020). A sazonalidade é uma característica frequente na demanda, causada por variações climáticas, datas comemorativas, entre outros fatores.…”
Section: Previsão De Demandaunclassified